Developmental changes of age-group swimmers
Age-group swimmers were measured to identify the order and rate of development of performance factors. 1. It is unusual to see an early-maturer become an elite world-class swimmer. The initial power and strength advantage is lost when normal and late-maturers achieve full growth. Late-maturers need to rely on technique to offset the early-maturer's physical advantage. It is to every swimmers' benefit to have a strong grounding in technique development prior to the onset of the adolescent growth spurt. 2. Muscle mass and power develops gradually after puberty. Early growth advantages are eventually lost. In the oldest age groups, the percentage of maximum power output that can be sustained during a race differentiates performance levels. 3. Anaerobic capacity is relatively inconsequential prior to puberty. At puberty the first growth surge in anaerobic capacity occurs. It then develops at a much slower rate, and then surges again as a final developmental stage. 4. Aerobic capacity is the first physiological factor to develop fully. It is established by the onset of the adolescent growth spurt (as early as 12 and as late as 15 years in males; for girls it is one to two years earlier). The major training emphasis prior to and during puberty should be endurance training. Once puberty is completed, the training emphasis should change gradually. Several programming implications can be derived from this study.